Parathyroid Adenoma Causing Hyperparathyroidism With Complications Of Multiple Fractures, Brown’s Tumour, Renal Calculi & Hydronephrosis - RADHAKRISHNAN PAULRAJ; HANNIEYA ELMO PAUL; SANDHYA SADAN PALANDE (International Journal of Pharma and Bio Sciences, 2012)
Primary Hyperparathyroidism can be present with various complications when diagnosed in a later stage of the disease. Radiological investigations, such as USG of the neck, Technetium 99m MIBI Scintigraphy, Magnetic Resonant Imaging (MRI), Computer Tomography (CT) scans, and X-rays of the cortical and cancellous bones, can be of great aid in screening the disease. The Tc99m MIBI Scintigraphy is a newer imaging modality to view any foci of increased vascularity and retention of traces of Tc99m[1] ,10. CT scan and MRI provide the location of the gland, and any enlargement, and may also reveal any ectopic parathyroid glands. In addition to radiological imaging, histopathological pictures -microscopy and macroscopic, in correlation with biochemical values of Parathyroid Hormone, serum Calcium, serum Magnesium, serum Phosphorus and Alkaline Phosphotase can confirm the diagnosis1. In this study we describe a case of Parathyroid adenoma, presenting as Primary Hyperparathyroidism in a middle-aged woman with complaints of myalgia, multiple swellings over the limbs, inability to stand upright from a sitting posture, and inability to walk. Investigations revealed multiple pathological fractures over the limbs, Brown’s tumour, renal calculi and hydronephrosis. Her sign and symptoms are typical of a Primary Hyperparathyroidism and its complications. As she is a symptomatic case of Primary Hyperparathyroidism, surgical removal of the parathyroid adenoma was required to control the parathyroid hormone levels, and to prevent further complications. Studies have shown that removal of the parathyroid adenoma, causing the elevated hormone levels, will cause a regression of the brown tumour.